Isolated recessive nail dysplasia caused by FZD6 mutations: report of three families and review of the literature. (1st December 2016) - Kasparis, C.; Reid, D.; Wilson, N. J.; Okur, V.; Cole, C.; Hansen, C. D.; Bosse, K.; Betz, R. C.; Khan, M.; Smith, F. J. D.
Summary: Congenital abnormalities of the nail are rare conditions that are most frequently associated with congenital ectodermal syndromes involving several of the epidermal appendages including the skin, teeth, hair and nails. Isolated recessive nail dysplasia (IRND) is much rarer but has recently been recognized as a condition resulting in 20‐nail dystrophy in the absence of other cutaneous or extracutaneous findings. A few case reports have identified mutations in the Frizzled 6 ( FZD6 ) gene in families presenting with abnormal nails consistent with IRND. These reports have highlighted the role of Wnt–FZD signalling in the process of nail formation. We report three families presenting with features of IRND, in whom we identified mutations in FZD6, including one previously unreported mutation.